The phenomenon of Minsk: the city space and the cultural narrative - Titarenko, Larissa; Shirokanova, Anna (Creativity Studies, 2011)
The article addresses the issue of cultural identification of Minsk as an Eastern European post-Soviet capital. In order to understand the city’s present it is necessary to consider the radical changes it underwent in the 20th century, including almost a total destruction, radical change in ethnic structure, rapid after-war spatial expansion and, lately, the intensive symbolic production as a post-Soviet capital. To identify the characteristic features of Minsk through the sociological lens, cultural theory as well as historical reconstruction and cross-national comparison are employed. The article seeks to reflect the organisation of space and cultural narrative produced in Minsk today, as well as to consider the common strategies of thinking about Minsk. The changing statuses of Minsk and its symbolic role in the last century necessitate a profound reconceptualization of Minsk as a phenomenon. The authors argue that the analysis of the ongoing changes in post-Soviet capitals (both in and out of the European Union (EU)) presupposes the reconstruction of their socio-cultural context. Minsko fenomenas: miesto erdvė ir kultūrinis naratyvas Santrauka. Straipsnyje susitelkiama į kultūrinį Minsko, kaip Rytų Europos posovietinės sostinės, tyrimą. Kad būtų galima suprasti miesto dabartį, būtina aptarti radikalias permainas, vykusias XX a., neišleidžiant iš akių kone visiškos destrukcijos, radikalių etninės struktūros pokyčių, sparčios pokarinės erdvės ekspansijos ir galiausiai intensyvios simbolinės gamybos kaip posovietinio kapitalo. Kad būtų nustatyta, kokie bruožai charakteringiausi Minskui sociologinėje perspektyvoje, pasitelkiama kultūros teorija, istorinė rekonstrukcija ir tarpnacionalinis palyginimas. Straipsnyje siekiama reflektuoti erdvės organizaciją ir kultūrinį naratyvą, nūdien produkuojamą Minske, taip pat apsvarstyti bendrąsias šio miesto tendencijas. Kintantis Minsko statusas ir simbolinis jo vaidmuo pastarajame amžiuje reikalauja naujaip ir nuodugniai konceptualizuoti šį miestą kaip fenomeną. Autorės tvirtina, kad vykstantys pokyčiai posovietinėse sostinėse (Europos Są jungoje ir anapus jos) turi įtakos jų sociokultūrinio konteksto rekonstravimui. Reikšminiai žodžiai: sostinė, miesto erdvė, kultūrinis naratyvas, Minskas, posovietinis kapitalas, vizualumas.